2007
DOI: 10.1111/j.1365-2427.2007.01855.x
|View full text |Cite
|
Sign up to set email alerts
|

Fish larvae, growth and biomass relationships in an Australian arid zone river: links between floodplains and waterholes

Abstract: 1. Floodplain inundation provides many benefits to fish assemblages of floodplain river systems, particularly those with a predictable annual flood pulse that drives yearly peaks in fish production. In arid-zone rivers, hydrological patterns are highly variable and the influence of irregular floods on fish production and floodplain energy subsidies may be less clear-cut. To investigate the importance of floodplain inundation to a dryland river fish assemblage, we sampled fish life stages on the floodplain of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 30 publications
7
121
1
Order By: Relevance
“…Thus, our results suggest that spawning of most fish occurs at a high water level and water runoff and when water temperature is appropriate. Flooding enhances recruitment by either directly stimulating spawning, or indirectly enhancing larval and juvenile survival by transporting larvae to habitats with rich food resources on the inundated floodplain (Harris & Gehrke, 1994;Balcombe et al, 2007). Our results showed that the abundance of larval fish peaked in May in the early flooding season.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Thus, our results suggest that spawning of most fish occurs at a high water level and water runoff and when water temperature is appropriate. Flooding enhances recruitment by either directly stimulating spawning, or indirectly enhancing larval and juvenile survival by transporting larvae to habitats with rich food resources on the inundated floodplain (Harris & Gehrke, 1994;Balcombe et al, 2007). Our results showed that the abundance of larval fish peaked in May in the early flooding season.…”
Section: Discussionsupporting
confidence: 58%
“…We suggest that the larger number of species and higher abundance of larval fish at AQ than at NJ reflect an influence of the connectivity of the Poyang Lake with the Yangtze River upstream of AQ, and the delayed bloom of larval fish and the occurrence of estuarine species at JJ reflect the influence of tidal intrusion from the estuary. Life histories of many fish species have evolved to adapt to the hydrological regimes of river-floodplain system by spawning in the river and nursing in the floodplain habitats (Fernandes, 1997;Balcombe et al, 2007;Osorio et al, 2011). Lateral connectivity between river and the floodplain habitats is essential for these fishes to complete their life cycles (Junk et al, 1989;Bayley, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stephen also has extensive experience working in the river systems that were studied and in other arid and semi-arid Australian systems [28,39,47].…”
Section: Author Contributionsmentioning
confidence: 99%
“…In California, the protracted availability of seasonal habitats coincides with the spawning period of many native fishes (Villa 1985;Moyle 2002). Thus, seasonal floodplains and other similar habitats peripheral to the mainstem of rivers and streams are increasingly recognized as important breeding and nursery areas for many species of freshwater fish (Turner et al 1994;Balcombe et al 2007). Seasonal inundation significantly increases the total amount of available aquatic habitat and provides greater habitat heterogeneity than is found in the main channel (Power et al 1995;Sommer et al 2002Sommer et al , 2004.…”
mentioning
confidence: 99%